Adenovirus Genotyping Based on Penton Gene Expression - Jawa, Basem (Journal of King Abdulaziz University: Medical Sciences, 2023)
Adenoviruses contain double-stranded DNA, and human adenoviruses are no exception. An individual’s immune status and the type of infection can determine the severity of adenovirus infections. There have been many successful vaccines developed using vectors derived from adenoviruses, including the COVID-19 vaccines manufactured by AstraZeneca and Johnson & Johnson, Ervebo, which uses an adenovirus vector to deliver a gene for the Ebola virus glycoprotein, Rabies vaccine, Imovax, which delivers the rabies virus glycoprotein gene using an adenovirus vector. As part of the icosahedral virus particle, the penton protein is encoded by the penton gene of the adenovirus. Additionally, the penton protein is required for initiation of virus entry into cells and virus attachment to host cells. Adenovirus HVR region limited typing was examined to determine the genotype of the virus. In order to construct phylogenetic trees for HAdV-D types 1 to 70, 9 isolates were typed, sequenced, and phylogenetic trees were constructed for the penton HVR loop regions that recorded a novelty strains that have not been reported previously. DNA extraction, PCR were conducted in this study with phylogenetic analysis.